2019
DOI: 10.3390/c5030045
|View full text |Cite
|
Sign up to set email alerts
|

Fluence Enhanced Optical Response of Ag Implanted Amorphous Carbon Thin Films

Abstract: Silver nanoparticles (NPs) are known to exhibit strong interaction with light photons because their surface conduction electrons undergo collective oscillations once photo-excited at specific wavelengths; the so-called surface plasmon resonance (SPR). Their incorporation into carbon-based material is shown to greatly influence the overall optical response of the matrix due to aggregation. In this paper, we studied the optical response of silver-irradiated amorphous carbon films due to varying fluence of 25 keV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Going to ''extended" C systems, the role of amorphous hydrogenated carbon (a-C:H) in reinforcing the promising biodegradable polymer polyhydroxybutyrate (PHB), was discussed in [15]. It was shown that stable layers of a-C:H up to 450 nm can be deposited on PHB with customizable properties dependent on the thickness and growth plasma, and correlated to the sp 2 /sp 3 ratio within a-C:H. In addition, a study of Ag-bombarded amorphous carbon films (Ag:a-C) to obtain composites was reported in [16]. The work highlights that the Ag nanoparticle aggregation/size modifies the overall optical response of the nanocomposite causing a blue shift of the surface plasmon resonance wavelength and the tuning of the optical response of the material exploitable for optical coatings and solar applications.…”
mentioning
confidence: 99%
“…Going to ''extended" C systems, the role of amorphous hydrogenated carbon (a-C:H) in reinforcing the promising biodegradable polymer polyhydroxybutyrate (PHB), was discussed in [15]. It was shown that stable layers of a-C:H up to 450 nm can be deposited on PHB with customizable properties dependent on the thickness and growth plasma, and correlated to the sp 2 /sp 3 ratio within a-C:H. In addition, a study of Ag-bombarded amorphous carbon films (Ag:a-C) to obtain composites was reported in [16]. The work highlights that the Ag nanoparticle aggregation/size modifies the overall optical response of the nanocomposite causing a blue shift of the surface plasmon resonance wavelength and the tuning of the optical response of the material exploitable for optical coatings and solar applications.…”
mentioning
confidence: 99%